The relationship between brand and consumer in social media: - Pretel Jiménez, Marilé (2019)
Emotions are part of the brands communication. The models provided to explain the influence process are often focused on cognitive processing, leaving the affective process aside. The present paper identifies the elements that are activated in the consumer mind while attending brand communication and how this process supports the creation of powerful brands. The study focus on the emotional evaluation of the Apple brand compare to Samsung brand. The three-factor model proposed by Thomson, MacInnis, y Park (2005) is used to measure the affect, passion and brand connection. The results show that the scale adaption to the Spanish sample achieves good psychometrics properties when applied to the selected brands. Apple displays better evaluation than Samsung from the emotional point of view and confirm its followers in social media have more emotional link than those who are not.